Beyond Patronage: Reconsidering Models of Practice - Hwang, Joyce; Bohm, Martha (UrbanNext, 2016)
This book explores contemporary architectural practices and design agendas that are being shaped or enabled by news forms of (3z(Bpatronage(3ys
Beyond Patronage, Essay, expanding design practices, Joyce Hwang, Martha Bohm, No Density, Politics and economics
Architect$1 (Bs challenge, Architect$1 (Bs role, Architecture, Cultural agitator, Developing policies, Discipline, Essay, Identity, Interdisciplinary design, Model, Modern urban Beijing, Practice, Timeless Model, University at Buffalos
https://lccn.loc.gov/2016462753
Keywords: Architectural Practice; Research